Are social media bad for your employees? Effects of at-work break activities on recovery experiences. (July 2021) - Cheng, Yi-Sung; Cho, Seonghee
Abstract: Since social media has become a fundamental part of the daily activities of people, the purpose of this study was to explore social media use by focusing on job demands that may explain why employees perceive social media are vital for them at work. Further, this study seeks to understand how employees use social media at work to experience recovery. Questionnaires were collected from current frontline hospitality non-managerial and managerial employees in the United States. Structural equation modeling was employed to analyze data. Results of the study confirm that at-work break activities including social and non-media break activities can be a channel for employees to experience recovery and deal with job demands. Moreover, the results suggest that at-work break activities are an important mediator between job demands and recovery experiences. Social media break activities also moderated the mediation effect of non-social media break activities between job demands and recovery experiences. Highlights: Job demands are an important trigger for employees to engage in at-work break activities. Psychological detachment and relaxation are two positive outcomes of social and non-social media break activities. Non-social media break activities had similar impacts to social media break activities on recovery experiences. Social media use could be an effective at-work recovery activity. A moderated mediation model has been tested and established.